Assessing the relationship between women's attitudes toward food waste prevention and their green diets - Eşer Durmaz, Sevinç; Bayındır Gümüş, Aylin; Nişancı Kılınç, Fatma; Ergenç Özdaş, Cansu (Frontiers in Nutrition, 2025)
BackgroundFood waste is one of the major obstacles to sustainable nutrition. The aim of this study is to examine the relationship between women's attitudes and behaviors toward preventing food waste and their green eating behaviors.MethodsThis study was conducted with 870 adult women aged 19–64 across Türkiye. Data collection was conducted in person through face-to-face interviews. A comprehensive questionnaire was administered to participants during the interviews. The questionnaire included questions on demographic and socioeconomic characteristics, green eating (GE), attitudes and behaviors toward preventing food waste (FWP), frequency of food waste from various food groups, frequency of food waste prevention actions (FWP-FA), and several anthropometric measurements [such as height, weight, waist circumference, and body mass index (BMI)]. Data obtained in the study were analyzed using the SPSS 29.0 statistical package.ResultsThe FWP mean scores of the participants are low in the 19 and 29 age group. The mean scores of GE [F(4, 865) = 2.338, p = 0.05] and FWP [F(4, 865) = 3.272, p = 0.011] differ significantly according to educational level. According to income levels, both GE mean scores [F(2, 865) = 4.298, p = 0.01] and FWP mean scores [F(2, 865) = 3.154, p = 0.043] differ significantly. While GE [F(3, 863) = 0.836, p = 0.47] mean scores did not differ according to BMI levels, FWP [F(3, 863) = 5.731, p = 0.001] mean scores differed significantly according to BMI levels.ConclusionsThe findings indicate that FWP has a significant positive effect GE, and that the combined influence of FWP and FWP-FA on GE is both strong and statistically significant. Additionally, waist circumference was found to have a small but significant negative impact on GE. Although BMI was analyzed as a potential mediator, it did not significantly mediate the relationship between FWP and GE. These results suggest that attitudes and behaviors aimed at reducing food waste are directly associated with green eating practices, while obesity-related indicators such as waist circumference may negatively influence this relationship.